2019
DOI: 10.1111/ijpo.12569
|View full text |Cite
|
Sign up to set email alerts
|

Association of breastfeeding and early exposure to sugar‐sweetened beverages with obesity prevalence in offspring born to mothers with and without gestational diabetes mellitus

Abstract: Background:The relationship of gestational diabetes mellitus (GDM), exclusive breastfeeding (EBF), and sugar-sweetened beverages (SSBs) on obesity prevalence in children has rarely been evaluated.Objective: This study examined the association of GDM status, EBF, and SSB with obesity prevalence in children (1-5 y).Methods: Data are from the 2014 Los Angeles County WIC Survey, which included 3707 mothers and their children (1-5 y). Results:Compared with GDM offspring who were not EBF, GDM offspring who were EBF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Carbonated soda drinks, flavoured fruit drinks and milk-based beverages are being consumed in increasing amounts by young children and have become major sources of added sugar in their diet [13]. A growing body of evidence suggests that high consumption of SSBs is significantly associated with low intakes of micronutrients [14,15], increased risk of dental caries [16], and risk of excess weight gain, and metabolic disorders in children [10,[17][18][19]. Moreover, numerous studies have also shown that dietary practices established in early childhood could persist into adolescence [20], and then into adulthood [21].…”
Section: Introductionmentioning
confidence: 99%
“…Carbonated soda drinks, flavoured fruit drinks and milk-based beverages are being consumed in increasing amounts by young children and have become major sources of added sugar in their diet [13]. A growing body of evidence suggests that high consumption of SSBs is significantly associated with low intakes of micronutrients [14,15], increased risk of dental caries [16], and risk of excess weight gain, and metabolic disorders in children [10,[17][18][19]. Moreover, numerous studies have also shown that dietary practices established in early childhood could persist into adolescence [20], and then into adulthood [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies did not assess infant dietary intake, except for maternal recall of BF; in these studies, older children who were exposed to GDM were investigated and the severity of GDM was not assessed. A cross-sectional study of WIC participants found a higher odds of obesity at 1-5 years of age in children who were exclusively breastfed with concurrent SSB intake, regardless of GDM exposure [11]. However, this study did not assess GDM severity or infant diet during the first year of life.…”
Section: Discussionmentioning
confidence: 89%
“…In 2015-2016, the prevalence of overweight and obesity among U.S. children and adolescents (aged 2-19 years) were 16.6% and 18.5%, respectively; while obesity prevalence was about 14% among children aged 2-5 years [4,5]. GDM and early life dietary behaviours such as limited breastfeeding (BF), limited exclusive BF (EBF) and other postnatal dietary habits may influence weight gain, obesity and metabolic disease among young children and adolescents [6][7][8][9][10][11]. Prospective studies of GDM infants show conflicting findings for BF measures and infant linear ponderal growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, relative to PF supply, studies are still scarce. A recent study observed that, in children exposed to gestational DM, BF only maintain its protection against childhood obesity if processed foods, like sugar-sweetened beverages intake, were also low [36].…”
Section: Discussionmentioning
confidence: 99%